Tinjauan Yuridis Restrukturisasi Hutang Dalam Perjanjian Kredit Pada Masa Pandemi Covid 19: (Studi di SMS Finance Cabang Mataram) - I Gusti Ayu Fanya; Aris Munandar (Private Law, 2022)
This research aims to find out the form of debt restructuring in pandemic covid-19 in SMS finance Branch of Mataram and the impact of restructuring to the credit agreement for the debtor. The method of this research is empirical legal research using statute, conceptual and sociological approaches. The result of this research experienced that based on the Financial Service Authority (OJK) Regulation Number 11/POJK.03/2020 concerning National Economic Stimulus as the policy concerning Countercyclical of the impact of spreading Corona Virus Diseases 2019. Debt restructuration is the effort to repair that is conducted in credit activity to debtor who finds the difficulties situation to fulfil the obligation. It provides to debtors who find the credit problems with certain criteria, for instance, debtor that still find the difficult situation the payment (main credit and/or credit interest) due to the decline financial condition causes some problems.